The silk of gorse spider mite Tetranychus lintearius represents a novel natural source of nanoparticles and biomaterials - Lozano-Pérez, Antonio Abel (Sci Rep, 2020)
Spider mites constitute an assemblage of well-known pests in agriculture, but are less known for their ability to spin silk of nanoscale diameters and high Young’s moduli. Here, we characterize silk of the gorse spider mite Tetranychus lintearius, which produces copious amounts of silk with nano-dimensions. We determined biophysical characteristics of the silk fibres and manufactured nanoparticles and biofilm derived from native silk. We determined silk structure using attenuated total reflectance Fourier transform infrared spectroscopy, and characterized silk nanoparticles using field emission scanning electron microscopy. Comparative studies using T. lintearius and silkworm silk nanoparticles and biofilm demonstrated that spider mite silk supports mammalian cell growth in vitro and that fluorescently labelled nanoparticles can enter cell cytoplasm. The potential for cytocompatibility demonstrated by this study, together with the prospect of recombinant silk production, opens a new avenue for biomedical application of this little-known silk.